ORIENTALISM AND ISLAM: A CRITICAL STUDY OF THE RELATIONSHIP BETWEEN PROPHET MUHAMMAD AND THE JEWS AS PRESENTED IN CHAPTER SIX OF MONTGOMERY WATT’SBOOK MUHAMMAD AT MEDINA - Masuwd, Mowafg; Ayad, Nahid; Albshkar, Hajer; Alsayd, Abdulnaser (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This research critically examines Montgomery Watt’s views on the Prophet’s biography, particularly his relationship with the Jews, in order to refute the misconceptions raised by Watt and other Orientalists who adopted similar perspectives. The study focuses on a critical analysis of Watt’s interpretations of the Prophet’s relationship with the Jews in Medina through a thorough reading of the sixth chapter of his book. The researchers present and objectively critique a selection of Watt’s views, highlighting the ambiguity and bias in his narrative. The study reveals the author’s lack of objectivity in his depiction of the Prophet’s biography, as he selectively frames events in a way that portrays the Jews as victims of the Arabs and Islam. Furthermore, the research aims to shed light on the intellectual and Orientalist influences that may have shaped Watt’s approach and analysis. يتناول هذا البحث آراء مونتجمري وات في السيرة النبوية خصوصا علاقة الرسول محمد صلى الله عليه وسلم باليهود بالنقد والتمحيص لرد الشبهات التي أثيرت من قبل مونتجمري وات وبعض المستشرقين الآخرين ممن تبنوا أفكارا مشابهة. تركز هذه الدراسة على تحليل نقدي لآراء مونتجمري وات في علاقة الرسول باليهود في المدينة من خلال قراءة متأنية للفصل السادس من كتابه. وقد قام الباحثون بعرض مجموعة من هذه الآراء مع نقدها نقدا موضوعيا يساهم في رفع الغموض وإظهار الموقف العدائي للمؤلف من الإسلام ونبي الإسلام حيث يتبين عدم موضوعية المؤلف في سرده للسيرة النبوي وتناوله إياها بنوع من التحيز والانتقائية ليصور اليهود كضحية للعرب والإسلام. كما تسعى الدراسة إلى تسليط الضوء على التأثيرات الفكرية والاستشراقية التي قد تكون الأساس الذي شكل توجهات وات وتحليله.